Sexual selection by female choice in guppies (Poecilia reticulata) - Brooks, Robert Clinton (My University, 1996)
I investigated some evolutionary implications of female mate choice in a feral population of guppies (Poecllia reticultuai. I performed correlative and manipulative experiments to establish the relationship between female mate choice and other sexually selective forces including iutermale aggression and sneak copulation, and the exaggerated secondary sex characters (ornaments) of male guppies. Orange (carotenoid) ornamentation is the best predictor of male attractiveness and mating success, a relationship which held under manipulation. Black (melanin) is sometimes correlated with male mating success. Mnnipulatiug the black area of males reveals that it is important to male attractiveness, and this appears to be in the form of a signal amplifier of male orangeness. This is the fi.st experimental evidence for a visual signal amplifier. For both orange and black areas, the relationship between absolute area and fluctuating asymmetry is positive and significant, suggesting that neither is n signal of male condition. These results arc Interpreted in the context of theories of the evolution of multiple male ornaments. Females are able to express their preference for orange with the first mature male they ever encounter, uuggestlng an important role for genetic determination in female preferences. This is corroborated by high repeatability of female mate choice behaviour. Experience modifies a female's preferences as she is able to adjust her response to a male in relation to the ornamentation of (at least) the previous male she saw. Mate copying has no mensurable effect on the outcome of female mate choice decisions.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg in fulfillment of the requirement for the degree of Doctor of Philosophy JOHANNESBURG January 1996
Keywords: Guppies; Sexual selection in animals; Fishes (Reproduction); Livebearers (Fish)